A multi‐scale approach to laminated microbial deposits in non‐marine carbonate environments through examples of the Cenozoic, north‐east Iberian Peninsula, Spain. (2nd May 2021) - Arenas‐Abad, Concha
Abstract: This contribution focusses on stromatolites and oncolites as tools to seek diverse environmental and climate information at different temporal scales. The scales are: (a) Low frequency, dealing with macroscopic and megascopic scales, and (b) high frequency, involving calendar and solar frequency bands. Two depositional environments are used for this purpose: (a) Fluvial and fluvial–lacustrine, which can develop under high to moderate gradients, and in low‐gradient conditions, and (b) lacustrine, subject to low‐gradient, hydrologically closed lake conditions. Several current and ancient examples in the Iberian Peninsula allow high‐frequency and low‐frequency analyses. Within the wedge‐shaped depositional units that fill the high‐ to moderate‐gradient, stepped fluvial systems, stromatolites form half domes and lenticular bodies, commonly at the wedge front. Oncolites are uncommon. These stromatolites developed in moderate to fast‐flowing water in stepped cascades and rapids. Their geometry and extent reflect the topography of the bedrock and later ongoing growth. In low‐gradient fluvial and fluvial‐(open) lacustrine systems the depositional units are tabular, low‐angle wedge‐shaped and lenticular and have great spatial facies variability. The dominant oncoid and coated‐stem limestones form gently lenticular stacked bodies, developed in wide, low to high‐sinuosity channels within wide tufaceous palustrine areas and small lakes. In the Ebro Basin saline carbonate lacustrine systems, stromatolites form thin planar to domed and stratiform bodies and are associated with muddy‐grainy laminated carbonates and very rare oncolites, together forming ramp‐shaped units that represent the inner fringes of high lake‐level deposits. This geometry reflects low‐gradient lake surface and shallow water conditions. Textural and structural features allow different ranks of laminae and types of lamination to be distinguished. Texture, together with the δ 13 C and δ 18 O values of consecutive laminae, are useful in distinguishing environmental and climate changes operating over different time spans. Periodicity analysis of lamination can help to discern any temporal significance in the lamination. Abstract : The focus of this contribution is on laminated microbial deposits in fluvial and lacustrine carbonate environments, in particular stromatolites and oncolites, and their relationships with other lithofacies, as tools to gather varied information, primarily environmental (i.e. depositional characters, type of sediment, depth, energy and chemical composition of water) and climatic, at different temporal scales. To achieve this purpose three types of sedimentary systems with a wide array of carbonate facies in the NE Iberian Peninsula are compared (fluvial, fluvio–lacustrine and saline lacustrine environments). In each case, the laminated microbial deposits form distinct 3D‐geometry bodies within the sedimentary units, and occur at specific positions in the vertical facies associations, from which environmental and hydrological significance can be inferred at macroscopic scale and expressed through conceptual facies models. Indeed the environmental, climatic and temporal significance of lamination is discussed from a multi‐proxy approach to these examples.